A study on the Barangay Loyola Heights Community's perception of the sustainainability of the Barangay Loyola Heights Community-based Toy Library - Victorio, Mico Paulo M.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study focused to determine the perception of the Barangay Loyola Heights Community towards the role of the toy library in consideration of its sustainability by identifying the strengths, weaknesses, opportunities, and threats; to know their views on sustainability and ways of approaching it; to identify ways in which the community can support and contribute to the toy library's sustainability, and; to determine the practices and strategies that the toy library must do to improve its programs and services.
In the study, survey questionnaire and interview schedule were used in the data collection. Respondents were children between ages three to seven; parents, guardians, and teachers who accompanied the children; the Toy Library administration and staff, and; the head of the Philippine Toy Library.
Based on the findings, the children, parents, guardians and teachers were perceived to be satisfied with the existence and the collection of the toy library in their community. In terms of sustainability, the Barangay Loyola Heights Community-based Toy Library lacked mission, goals and objectives, development policy, and skilled personnel to manage the library operation. However, it was supported by the local government on its budget, venue, and utility costs. The collection, other resources, and networking and linkages were managed and provided by the Philippine Toy Library.
The problem that may hinder the toy library's sustainability were lack of programs like storytelling, art workshops, and others, to support the toy library program. Another is the community involvement which was one of the key determinants in the sustainability of the toy library. The community provides the toys, equipment, and furniture through donation. They also partake in the decision-making development, and management of the toy library.
Full and continuous support and commitment by the members of the community, namely, the officials and families altogether, are needed for the toy library to operate. Without them, the toy library would eventually cease to function.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Toy lending libraries -- Philippines -- Quezon City